Chinese Experts Consensus on Pre-examination and Triage in Dermatology Clinics during the COVID-19 Outbreak# - Lin Ma; Chinese Society of Dermatology; Gang Wang; Qi-Ri Mu; Yu-Ping Ran; Quan-Zhong Liu; Sheng-Xiang Xiao; Xue-Jun Zhang; Jian-Zhong Zhang; Fu-Ren Zhang; Li He; Ai-Jun Chen; et al. (Wolters Kluwer Health, 2020)
Abstract. The SARS-CoV-2 infection has brought a great challenge in prevention and control of the national epidemic of coronavirus disease 2019 (COVID-19) in China. During the COVID-19 epidemic, properly carrying out pre-examination and triage for patients with skin lesions and fever has become a practical problem encountered in hospitals for skin diseases and dermatology clinics in general hospitals. Some of the carriers of the SARS-CoV-2 and patients with COVID-19 in the early stage may not present with any symptoms of COVID-19, while certain other skin diseases can also cause fever. Therefore, to properly deal with the patients presenting at dermatology clinics, the Chinese Society of Dermatology organized experts to formulate principles and procedures for the pre-examination and triage of patients at dermatology clinics during the COVID-19 epidemic.